Lessons in project management - Mochal, Tom 1957-; Mochal, Jeff, 1974- (Apress, 2011)
Most of the project management books on the market are basically textbooks. They are dry to begin with, and don't focus on the practical advice that most people need to run their projects. Lessons in Project Management, Second Edition does not assume that you are a project manager building a nuclear reactor or sending a man to the moon. Instead, it focuses on the millions of people who manage normal, medium-to-large projects on an ongoing basis.   Each case study in Lessons in Project Management contains an accessible, easy-to-read analysis of the challenges of real-world project management. Each problem is presented, then followed by an examination of the solution, written in easy-to-understand language. The format allows you to more easily relate to the book, since it brings into play a project scenario with practical project management lessons to be learned. You'll also recognize recurring characters who appear in multiple stories, and you'll start to develop some empathy for and interest in their struggles.